Total synthesis of mangiferaelactone - Vadhadiya, Paresh M.; Ramana, C. V. (Tetrahedron Letters, 2014)
Herein we document the first total synthesis of mangiferaelactone and thus establish its absolute configuration. The central nonenolide ring was constructed using ring closing metathesis and Yamaguchi esterification. The key alcohol fragment was synthesized by the Bernet-Vasella fragmentation of C-ribofuranoside. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Bernet-Vasella fragmentation; Nonenolide; Ring closing metathesis; Total synthesis; Yamaguchi protocol